2022
DOI: 10.3390/genes13122357
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies in Sunflower: Towards Sclerotinia sclerotiorum and Diaporthe/Phomopsis Resistance Breeding

Abstract: Diseases caused by necrotrophic fungi, such as the cosmopolitan Sclerotinia sclerotiorum and the Diaporthe/Phomopsis complex, are among the most destructive diseases of sunflower worldwide. The lack of complete resistance combined with the inefficiency of chemical control makes assisted breeding the best strategy for disease control. In this work, we present an integrated genome-wide association (GWA) study investigating the response of a diverse panel of sunflower inbred lines to both pathogens. Phenotypic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Previous studies identified various loci involved in the quantitative resistance to V. dahliae and S. sclerotiorum, mostly through comprehensive analysis in biparental mapping, association mapping, or transcriptome differential expression studies [25,26,[30][31][32]55]. In an attempt to provide a biological context to the candidate genes derived either by colocalizing with a molecular marker in GWAS studies or by being located in between markers in QTL studies, we focused on the candidates predicted to be related to defense functions in our modules of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified various loci involved in the quantitative resistance to V. dahliae and S. sclerotiorum, mostly through comprehensive analysis in biparental mapping, association mapping, or transcriptome differential expression studies [25,26,[30][31][32]55]. In an attempt to provide a biological context to the candidate genes derived either by colocalizing with a molecular marker in GWAS studies or by being located in between markers in QTL studies, we focused on the candidates predicted to be related to defense functions in our modules of interest.…”
Section: Discussionmentioning
confidence: 99%
“…After completion and analysis of our networks, we compiled lists of candidate genes previously associated with resistance to the sunflower fungal pathogens V. dahliae and S. sclerotiorum to assess the performance of our networks in predicting gene functions. We collected three groups of genes: Group A, a list of 26 candidate genes from Filippi et al [25]; Group B, genes that were close (±1 megabase) to markers from four QTL mapping and genome-wide association studies: Zubrzycki et al [30], Filippi et al [25], Filippi et al [31], and unpublished data from Montecchia et al; and Group C, genes that were in between markers flanking QTL regions from the work of Talukder et al [32]. It is noteworthy that groups B and C employed different germplasm in their respective studies, which allows for a broader range of genetic characteristics to be captured.…”
Section: Functional Prediction Of Candidate Genes Associated With Res...mentioning
confidence: 99%
“…Previous studies identified various loci involved in the quantitative resistance to V. dahliae and S. sclerotiorum, mostly through comprehensive analysis in biparental mapping, association mapping, or transcriptome differential expression studies [25,26,[30][31][32]46] (citas). In an attempt to provide a biological context to the candidate genes derived either by co-localizing with a molecular marker in GWAS studies or by being located in between markers of QTL studies, we focused on the candidates predicted as related to defense functions in our modules of interest.…”
Section: Discussionmentioning
confidence: 99%
“…After completion and analysis of our networks, we compiled lists of candidate genes previously associated with resistance to sunflower fungal pathogens V. dahliae and S. sclerotiorum to assess the performance of our networks in predicting gene functions. We collected three groups of genes: Group A, a list of 26 candidate genes from Filippi et al (2020) [25]; Group B, genes that were close (±1 megabase) to markers from four QTL mapping and genome-wide association studies: [25,30,31]; and Group C, genes that were in between markers flanking QTL regions from one study [32]. It is noteworthy that group B and group C employed different germplasm in their respective studies which allows for a broader range of genetic characteristics to be captured.…”
Section: Functional Prediction Of Candidate Genes Associated With Res...mentioning
confidence: 99%